Particle/cell separation on microfluidic platforms based on centrifugation effect: a review - Al-Faqheri, Wisam; Thio, Gilbert Tzer Hwai; Mohammad, Ameen Qasaimeh; Dietzel, Andreas; Madou, Marc; Al-Halhouli, Ala’aldeen (Springer International Publishing AG, 2017)
Particle/cell separation in heterogeneous mixtures including biological samples is a standard sample preparation step for various biomedical assays. A wide range of microfluidic-based methods have been proposed for particle/cell sorting and isolation. Two promising microfluidic platforms for this task are microfluidic chips and centrifugal microfluidic disks. In this review, we focus on particle/cell isolation methods that are based on liquid centrifugation phenomena. Under this category, we reviewed particle/cell sorting methods which have been performed on centrifugal microfluidic platforms, and inertial microfluidic platforms that contain spiral channels and multi-orifice channels. All of these platforms implement a form of centrifuge-based particle/cell separation: either physical platform centrifugation in the case of centrifugal microfluidic platforms or liquid centrifugation due to Dean drag force in the case of inertial microfluidics. Centrifugal microfluidic platforms are suitable for cases where the preparation step of a raw sample is required to be integrated on the same platform. However, the limited available space on the platform is the main disadvantage, especially when high sample volume is required. On the other hand, inertial microfluidics (spiral and multi-orifice) showed various advantages such as simple design and fabrication, the ability to process large sample volume, high throughput, high recovery rate, and the ability for multiplexing for improved performance. However, the utilization of syringe pump can reduce the portability options of the platform. In conclusion, the requirement of each application should be carefully considered prior to platform selection.